PERANCANGAN SISTEM INFORMASI PEMBAYARAN BIAYA PENDIDIKAN DI UNIVERSITAS MA’SOEM JATINANGOR - Firman Hamdani (INTERNAL (Information System Journal), 2019)
Ma'soem University is a university located in the Al Ma'soem Foundation Bandung (YAB). At present Ma'soem University has four Faculties, namely the Faculties: Computers, Faperta, Islamic Business Economics, Teacher Training and Education. With the increasing number of new students every year around 350 people per class, the Ma'soem University finance department must have an information system design that can help and facilitate financial acceptance and report preparation so that it can be produced quickly. The finance department of Ma'soem University is currently using its manual financial management system, where every student who makes a payment is recorded on a proof of payment invoice which is then recapitulated for financial statements. Based on these considerations, it is deemed necessary to design a financial information system that is expected to help facilitate the process of payment of education costs at Ma’soem University.In this Education Fee Payment Information System Design, the writer uses the SDLC (System Development Life Cycle) system development life cycle method, which consists of five stages: analysis, design, code, testing and implementation.The design of this information system is expected to handle the payment of tuition fees with various facilities, namely: can facilitate the search for data of students who have not paid tuition fees, can avoid duplication of data and calculation errors in education costs and is expected to present reports of tuition payment payments quickly and automatically.Ma'soem University is a university located in the Al Ma'soem Foundation Bandung (YAB). At present Ma'soem University has four Faculties, namely the Faculties: Computers, Faperta, Islamic Business Economics, Teacher Training and Education. With the increasing number of new students every year around 350 people per class, the Ma'soem University finance department must have an information system design that can help and facilitate financial acceptance and report preparation so that it can be produced quickly. The finance department of Ma'soem University is currently using its manual financial management system, where every student who makes a payment is recorded on a proof of payment invoice which is then recapitulated for financial statements. Based on these considerations, it is deemed necessary to design a financial information system that is expected to help facilitate the process of payment of education costs at Ma’soem University.               In this Education Fee Payment Information System Design, the writer uses the SDLC (System Development Life Cycle) system development life cycle method, which consists of five stages: analysis, design, code, testing and implementation.            The design of this information system is expected to handle the payment of tuition fees with various facilities, namely: can facilitate the search for data of students who have not paid tuition fees, can avoid duplication of data and calculation errors in education costs and is expected to present reports of tuition payment payments quickly and automatically.